OKlahoma Nitrone-007: novel treatment for diffuse intrinsic pontine glioma - Thomas, Lincy (J Transl Med, 2020)
BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is the most common brainstem cancer in childhood. This rapidly progressing brainstem glioma holds a very dismal prognosis with median survival of less than 1 year. Despite extensive research, no significant therapeutic advancements have been made to improve overall survival in DIPG patients. METHODS: Here, we used an orthotopic xenograft pediatric DIPG (HSJD-DIPG-007) mouse model to monitor the effects of anti-cancer agent, OKlahoma Nitrone-007 (OKN-007), as an inhibitor of tumor growth after 28 days of treatment. Using magnetic resonance imaging (MRI), we confirmed the previously described efficacy of LDN-193189, a known activin A receptor, type I (ACVR1) inhibitor, in decreasing tumor burden and found that OKN-007 was equally efficacious. RESULTS: After 28 days of treatment, the tumor volumes were significantly decreased in OKN-007 treated mice (p < 0.01). The apparent diffusion coefficient (ADC), as a measure of tissue structural alterations, was significantly decreased in OKN-007 treated tumor-bearing mice (p < 0.0001). Histological analysis also showed a significant decrease in CD34 expression, essential for angiogenesis, of OKN-007 treated mice (p < 0.05) compared to LDN-193189 treated mice. OKN-007-treated mice also significantly decreased protein expression of the human nuclear antigen (HNA) (p < 0.001), ACVR1 (p < 0.0001), and c-MET (p < 0.05), as well as significantly increased expression of cleaved caspase 3 (p < 0.001) and histone H3 K27-trimethylation (p < 0.01), compared to untreated mouse tumors. CONCLUSIONS: With the dismal prognosis and limited effective chemotherapy available for DIPG, there is significant room for continued research studies, and OKN-007 merits further exploration as a therapeutic agent.